Empowerment of Family Welfare Empowerment Groups Through Local Potential-Based Entrepreneurship Training - Muhammad Fadhil; Fifi Nurafifah Ibrahim; Mutmainna Mutmainna; Putri Salsabila (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to improve the entrepreneurial capacity of PKK mothers in Padang Lampe Village through training based on local potential, encourage the use of village resources for independent business development, and strengthen the family economy. Research Design and Methodology: The research used a descriptive-qualitative approach with participatory methods, involving Family Welfare Empowerment (PKK) mothers as the main participants, along with the village government and local stakeholders. The activity lasted three months, spanning the stages of preparation, training, mentoring, and evaluation. Data was collected through observation, interviews, documentation, and product evaluation. Findings and Discussion: The study's results show that local, potential-based entrepreneurship training can improve participants' knowledge, production skills, and packaging skills. Participants can recognize the potential of their villages and turn it into products of economic value, while also demonstrating increased motivation, collaboration, and readiness to form new businesses. This program also produced an Entrepreneurship Module that can be used as a sustainable guide. Implications: This activity strengthens the village entrepreneurship ecosystem by increasing women's capacity, leveraging local potential, and providing institutional support to villages. This program can be used as an implementable model for community empowerment based on local resources in other regions.